Who profits from windfalls in oil tax revenue? Inequality, protests, and the role of corruption - Michael Alexeev; Nikita Zakharov (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
We investigate the relationship between oil windfalls and income inequality using the subnational data of one of the resource-richest and most unequal countries in the world – Russia. While previous literature produced contradictory findings due to the use of an aggregate measure of oil rents mainly in cross-national settings, we focus exclusively on oil rents that accrue to the subnational governments across one country. Our estimation strategy takes advantage of the two specific features of Russian oil taxation: 1) the policy change when sharing oil extraction taxes with local budgets was discontinued; and 2) the oil tax formula being tied directly to the international oil prices making oil price shocks an exogenous measure of change in oil rents. When we look at the period with oil tax revenues shared with the regional governments, we find that oil windfalls had increased income inequality and benefited the wealthiest quintile of the population in regions with more intense rent-seeking. Further, positive price shocks combined with greater rent-seeking reduced the share of labor income but increased the income share from unidentified sources traditionally associated with corruption. These effects of oil windfalls disappeared after the Russian government discontinued oil tax revenue sharing with regional governments. Finally, we examine some political implications of rising inequality due to the appropriation of oil windfalls. We find a positive effect of rising inequality on the frequency of protests associated with grievances among the poor and disadvantaged social groups; this effect, however, exists only in relatively democratic regions.
URN:NBN:fi:bof-202201251035
Keywords: D63; D73; Q35; Q38; P48; 330; oil; decentralized revenues; income inequality; corruption; protest; Russia